KIF1C mutations in two families with hereditary spastic paraparesis and cerebellar dysfunction. Issue 2 (6th December 2013) - Dor, Talya; Cinnamon, Yuval; Raymond, Laure; Shaag, Avraham; Bouslam, Naima; Bouhouche, Ahmed; Gaussen, Marion; Meyer, Vincent; Durr, Alexandra; Brice, Alexis; Benomar, Ali; Stevanin, Giovanni; et al.
Abstract : Background: Hereditary spastic paraparesis (HSP) (syn. Hereditary spastic paraplegia, SPG) are a group of genetic disorders characterised by spasticity of the lower limbs due to pyramidal tract dysfunction. Nearly 60 disease loci have been identified, which include mutations in two genes ( KIF5A and KIF1A ) that encode motor proteins of the kinesin superfamily. Here we report a novel genetic defect in KIF1C of patients with spastic paraparesis and cerebellar dysfunction in two consanguineous families of Palestinian and Moroccan ancestry. Methods and results: We performed autozygosity mapping in a Palestinian and classic linkage analysis in a Moroccan family and found a locus on chromosome 17 that had previously been associated with spastic ataxia type 2 (SPAX2, OMIM %611302). Whole-exome sequencing revealed two homozygous mutations in KIF1C that were absent among controls: a nonsense mutation (c.2191C>T, p.Arg731*) that segregated with the disease phenotype in the Palestinian kindred resulted in the entire absence of KIF1C protein from the patient's fibroblasts, and a missense variant (c.505C>T, p.Arg169Trp) affecting a conserved amino acid of the motor domain that was found in the Moroccan kindred. Conclusions: Kinesin genes encode a family of cargo/motor proteins and are known to cause HSP if mutated. Here we identified nonsense and missense mutations in a further member of this protein family. The KIF1C mutation is associated with a HSP subtype (SPAX2/SAX2) that combines spastic paraplegia and weakness with cerebellar dysfunction.